The role of family members in rural adult education programme / Wan Hanisah Wan Ismail - Wan Ismail, Wan Hanisah (Universiti Teknologi MARA, Pahang, 1996)
The success of extension work very much depends on the roles and function of the family members. These include men, women and youth. In the rural community each member of the family unit has his/her own unique influence in the process of decision-making. This paper tries to describe and highlight some of the roles and influence each of the above family members have on the success of rural extension or adult education.